Analisis Yuridis Terhadap Penggunaan Pay Later di Aplikasi Shopee: Perspektif Mazhab al-Syafi’i - Rahayu, Ayu; Aisyah, Siti (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
In e-commerce there is one part that is in great demand today, namely the marketplace. One of the marketplaces that is in great demand by the Indonesian people, especially is Shopee. Shopee also provides various very interesting features on the Shopee mobile application, one of which is Shopee Pay Later. Credit available on Shopee Pay Later is the application of the qardh contract in Islamic law. The purpose of this study is to find out the features that exist in the Shopee marketplace, to understand the mechanism of using "Pay Later" in the Shopee marketplace and to find out Imam Syafi'i's thoughts on the use of payments later. This research is qualitative research with data collection using library research methods and normative approaches. The result of this research is that Bank Indonesia as a macroprudential institution has regulated the validity of Shopee Pay Later through Bank Indonesia Letter No.20/293/DKSP/Srt/B on August 8, 2018. Thus, the implementation of Shopee Pay Later is official and has obtained permission from Bank Indonesia. Based on Islamic law, the pillars and conditions of buying and selling in the practice of Shopee Pay Later credit from the Shopee marketplace do not contradict or violate the legal terms of buying and selling, the trade has met the terms and conditions. According to Imam Shafi'i, buying and selling like this is legal and the buyer has the right to do khiyar when there is a difference between the specifications of the goods and the goods when they come. He also stated in his qaul jadeed that the sale and purchase of this type was not legal. There is a hadith narrated from Abu Hurayrah that the Holy Prophet(sa) forbade everything that is unknown. Another reason is that the trade is included in the no gharar. Then it is not legal to buy and sell when it is unknown from its nature.